The Application of Graphene Oxide Nanoarchitectures in the Treatment of Cancer: Phototherapy, Immunotherapy, and the Development of Vaccines - Bhattacharya, Sankha; Belemkar, Sateesh; Prajapati, Bhupendra G. (Current Medicinal Chemistry, 2024)
Nanoparticles have been crucial in redesigning tumour eradication techniques, and recent advances in cancer research have accelerated the creation and integration of multifunctional nanostructures. In the fight against treatment resistance, which has reduced the effectiveness of traditional radiation and chemotherapy, this paradigm change is of utmost importance. Graphene oxide (GO) is one of several nanoparticles made of carbon that has made a splash in the medical field. It offers potential new ways to treat cancer thanks to its nanostructures, which can precisely transfer genetic elements and therapeutic chemicals to tumour areas. Encapsulating genes, protecting them from degradation, and promoting effective genetic uptake by cancer cells are two of GO nanostructures' greatest strengths, in addition to improving drug pharmacokinetics and bioavailability by concentrating therapeutic compounds at particular tumour regions. In addition, photodynamic treatment (PDT) and photothermal therapy (PTT), which use GO nanoparticles to reduce carcinogenesis, have greatly slowed tumour growth due to GO's phototherapy capabilities. In addition to their potential medical uses, GO nanoparticles are attractive vaccine candidates due to their ability to stimulate cellular and innate immunity. These nanoparticles can be used to detect, diagnose, and eradicate cancer because they respond to certain stimuli. The numerous advantages of GO nanoparticles for tumour eradication are attributed in large part to their primary route of internalisation through endocytosis, which guarantees accurate delivery to target locations. The revolutionary potential of multifunctional nanostructures in cancer treatment is highlighted in this extensive compendium that examines current oncological breakthroughs.
Keywords: immunotherapy